Twin Pregnancies, Crown-rump Length and Birthweight Discordancy: The Influence of Chorionicity - Nunes, JS (2020)
Objective: The purpose of the present study was to analyze the influence of chorionicity in the biometric parameters crown-rump length (CRL), birthweight (BW), crown-rump length discordancy (CRLD) and birthweight discordancy (BWD), determine the correlation between these latter two in cases of intertwin discordancy, and to analyze the influence of chronicity in the presence of these discordancies with clinical relevance (> 10% and > 15%, respectively). Methods: The present study was a retrospective study based on the twin pregnancy database of the Centro Hospitalar S. João (2010-2015), including 486 fetuses among 66 monochorionic (MC) and 177 dichorionic gestations (DC). The inclusion criteria were multiple pregnancies with 2 fetuses and healthy twin gestations. The exclusion criteria were trichorionic gestations and pregnancies with inconclusive chorionicity, multiple pregnancy with ≥ 3 fetuses and pathological twin gestations. Results: No statistically significant difference was found in BW (p = 0.09) and in its discordancy (p = 0.06) nor in CRL (p = 0.48) and its discordancy (p = 0.74) between MCs and DCs. Crown-rump length discordancy and birthweight discordancy were correlated by the regression line "BWD = 0.8864 x CRLD + 0.0743," with r2 = 0.1599. Crown-rump length discordancy > 10% was found in 7.58% of monochorionic and in 13.56% of dichorionic twins. Birthweight discordancy > 15% was detected in 16.67% of monochorionic and in 31.64% of dichorionic twins. Conclusion: No statistically significant influence of chorionicity was identified in both birthweight and birthweight discordancy, as in crown-rump length and crown-rump length discordancy. Birthweight discordancy was correlated to crown-rump length discordancy in 20% of cases.